The global impact of china's international strategy in the food sector - Brum, Argemiro Luís (2025)
Amid the current international disorder, China's new Belt and Road Initiative (BRI) has garnered attention as a global strategy reflecting its growing political and economic power. This essay adopts a "food regime" approach to analyze these developments. It explores two related dimensions: the first focuses on how China is addressing future food security needs, both domestically and internationally; and the second situates China's recent "going out" policy in the context of global food regime transitioning.